Can e-books support low SES parental mediation to enrich children's vocabulary?. Issue 3 (June 2019) - Korat, Ofra; Shneor, Daphna
This study examines whether an e-book with a dictionary could support parents' mediation of new words during shared book reading, more than the child's independent reading of an e-book with and without a dictionary. The participants included 128 kindergartners and 64 mothers who were randomly divided into four groups: independent reading of the e-book with a dictionary; joint mother–child reading of the e-book without a dictionary; joint mother–child reading of the e-book with a dictionary, and independent reading of the e-book without a dictionary (control). For each target word, the dictionary presented (1) word meaning, (2) word meaning within the story context, and (3) a combined meaning. Pre- and posttests included receptive and expressive understanding of the dictionary words. E-books were read four times. Reading the e-book with a dictionary and maternal mediation was the most effective for receptive and expressive word learning, followed by independent reading with the dictionary. Mothers who read the e-book with a dictionary mediated at a higher level than mothers who read without a dictionary. The intervention contributed to advancement in learning new words beyond children's initial vocabulary level. The research implications are presented in the discussion.